Perancangan Sistem PPIC di PT. Mustikarama Citraperdana - Yuliani, Novia Veronika; Palit, Herry Christian (Jurnal Titra, 2015)
PT. Mustikarama Citraperdana is a manufacturing industry that producesÂ safety box. This company has been developing which is known from the increase of demand, production volume, and also the types of product. Problem faced by PT. Mustikarama Citraperdana is sending customer order does not match the shipment date by a percentage of 52.44%. Initial observations, inaccuracy of time in order delivery caused by the production planning problem that is not appropriate.This thesis will design improvements to overcome the problem of production planning that caused the company experienced difficulties in the form of an order sending customer order does not match the shipment date. The design improvements are given in the form of production planning and inventory control of raw materials.